IMPLEMENTATION OF REGENT REGULATION NUMBER 72 OF 2022 CONCERNING LEBAK LEBUNG AUCTION PROCEDURES IN MUSI BANYUASIN REGENCY - Mari Guaninta W.S; Ardiyan Saptawan; Raniasa Putra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The general lebak lebung auction is an area consisting of lebak, lebung, rivers and nyurung land (the term ex marga nyurung land is land that comes from/because of mud) which is naturally in the deep water season and a breeding ground for fish or other biota. This paper aims to describe and analyze the implementation of policies on the procedures for implementing lebak lebung auctions in 4 sub-districts in Sekayu District, Musi Banyuasin Regency. The research method used in this study is descriptive qualitative. The results of this study are that the implementation of policies on the procedures for implementing Lebak Lebung auctions in 4 sub-districts in Sekayu District has not been optimal due to the ineffective communication of policy makers and implementers, the low quality of human resources implementing the policy, and conflicts between farmers and land owners around Lebak Lebung and Rivers. To overcome these obstacles, the Regional Government is expected to better supervise the management of objects and improve coordination between Policy auction makers and implementers.